PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KELURAHAN GRATITUNON - -, Siti Hikmatul Iklima (KINDAI, 2024)
The role of employees here is one of the main keys to the success or failure of a government organization. In administering government, the role of employees is influenced by Leadership style and Work Motivation. In this way, the performance of employees must be considered so that failure does not occur in carrying out the duties of government organizations. The aim of this research is to analyze the influence of Leadership style and Work Motivation on employee performance in Gratitunon Village. This research uses a sampling method which is carried out by taking the entire population of 52 respondents. Data collection was carried out using interview techniques and questionnaire collection. The results of this research show that Leadership Style has a positive and significant effect on employee performance, Work Motivation has a positive and significant effect on employee performance.